Comprehensive Frameworks for Addressing Climate Change Impacts on Water Resources Using AI-Driven IoT Networks to Support Public Health and Sustainability Initiatives - Ayodeji Idowu Taiwo; Lawani Raymond Isi; Michael Okereke; Oludayo Sofoluwe; Gilbert Isaac Tokunbo Olugbemi; Nkese Amos Essien (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Climate change poses significant challenges to global water resources, impacting their availability, quality, and reliability. These disruptions have profound implications for public health, including the proliferation of waterborne diseases and heightened risks from water scarcity. This paper explores the role of AI-driven IoT networks as transformative tools in addressing these challenges. These technologies optimize water resource management, support sustainable use, and mitigate public health risks by enabling real-time data collection, advanced analytics, and predictive insights. Furthermore, the integration of AI-driven IoT systems fosters the conservation of ecosystems and enhances resilience against climate-induced stresses. The paper also underscores the critical need for policy development, infrastructure investments, and community engagement to ensure these technologies’ equitable and effective deployment. Recommendations include fostering interdisciplinary research, promoting international cooperation, and implementing scalable pilot projects to address the complex interplay between climate change, water resource management, public health, and sustainability.